2019
DOI: 10.1101/533083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic CRMP2 regulation of CaV2.2 in the prefrontal cortex contributes to the reinstatement of cocaine seeking

Abstract: 227/250 words) Cocaine addiction is a major health concern with limited effective treatment options. A better understanding of mechanisms underlying relapse may help inform the development of new pharmacotherapies. Emerging evidence suggests that collapsin response mediator protein 2 (CRMP2) regulates presynaptic excitatory neurotransmission and contributes to pathological changes during diseases, such as neuropathic pain and substance use disorders. We examined the role of CRMP2 and its interactions with a kn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…By contrast, this locus was fine-mapped to two variants in high LD with rs16969968 for CigDay (r 2 = 0.84 and 0.86), suggesting that the variants underlying this signal for smoking initiation may be distinct from those for cigarettes per day. We also found a novel association between SmkInit and CACNA1B, which encodes a voltage-gated calcium channel (Ca v 2.2) that controls neuronal neurotransmitter release and has been associated with cocaine reinstatement 13 , increased aggression and vigilance, and reduced startle and exploration 14 . CACNA1B is linked to multiple psychiatric disorders, including schizophrenia, bipolar disorder and autism spectrum disorders [15][16][17] .…”
Section: Multi-ancestry Meta-analysismentioning
confidence: 87%
“…By contrast, this locus was fine-mapped to two variants in high LD with rs16969968 for CigDay (r 2 = 0.84 and 0.86), suggesting that the variants underlying this signal for smoking initiation may be distinct from those for cigarettes per day. We also found a novel association between SmkInit and CACNA1B, which encodes a voltage-gated calcium channel (Ca v 2.2) that controls neuronal neurotransmitter release and has been associated with cocaine reinstatement 13 , increased aggression and vigilance, and reduced startle and exploration 14 . CACNA1B is linked to multiple psychiatric disorders, including schizophrenia, bipolar disorder and autism spectrum disorders [15][16][17] .…”
Section: Multi-ancestry Meta-analysismentioning
confidence: 87%
“…The receptor might also be part of a group of modulators that localize Ca V 2.2 to postsynaptic sites, particularly in layer V/VI pyramidal neurons of the mPFC. It was recently shown that the collapsing response mediator protein 2 (CRMP2) augments Ca V 2.2 protein in PFC neurons, an effect tied to cue reinstatement after cocaine self-administration extinction ( Buchta et al, 2020 ). Thus, it is possible that Ca V 2.2, a typically presynaptic calcium channel, is playing a noncanonical role at postsynaptic sites in PFC neurons, and that D1R, among other modulators, stabilizes Ca V 2.2 protein at these sites.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are few effective pharmacological treatments available for cocaine use disorders, and frequently, psychosocial interventions in combination with pharmacotherapy are needed (Kampman, 2019). Studies performed in mice have pinpointed multiple potential therapeutic approaches for the reinstatement of cocaine-seeking behavior, targeting the reward circuit (Buchta et al, 2020). In humans, treatment with bupropion, topiramate, or disulfiram has been widely used.…”
Section: Discussionmentioning
confidence: 99%